Eksplorasi Strategi Guru dalam Mengajarkan Konsep IPA dalam abad ke-21 di Sekolah Dasar - Addurun Nafis Firdaus; Alim Amin Fathan; Cresna Shafa Saiddina; Siti Zalfa Pratiwi; Yazid Fadhilah (Lembag, 2025)
The 21st century is characterized by globalization and technological advances that require students to have critical thinking abilities as part of 21st century skills, such as digital literacy, creative thinking, effective communication, and high productivity. These abilities are important to help students solve problems logically and effectively. For this reason, educators need to create relevant learning scenarios, one of which is through the project-based learning (PjBL) model (Hartini 2017), which is centered on solving problem-based projects. However, students' critical thinking skills in science learning in elementary schools are still not optimal due to the lack of appropriate learning media. This research uses a literature review method using a qualitative approach, explaining that various kinds of digital media inventions, such as educational games, videos, YouTube, PowerPoint, AR/VR, & educational implementation (Ruang Guru, Quipper School, Kelas Pintar), can be effective in improving students' critical thinking skills in science learning.